Longitudinal faster anxiety progression of GBA variant carriers in the early Parkinson’s disease cohort - Sang, Shushan; Ba, Yunpeng; Yang, Nannan (Frontiers in Neuroscience, 2024)
Objective: Anxiety symptoms are prevalent neuropsychiatric manifestations in Parkinson's disease (PD) and impact the motor complications development. Our aim was to evaluate the association of GBA variants with the anxiety development in early PD cohort.Methods: This cohort study used data from the Parkinson Progression Marker Initiative. The primary outcome anxiety was assessed by State-Trait Anxiety Inventory (STAI). The association of GBA and longitudinal change in STAI total score were examined using linear mixed-effects models and the association of GBA and anxiety progression were examined using Cox survival analysis.Results:A total of 385 patients with PD got included in this study, 39 of them were GBA variants carriers and 346 were idiopathic PD without GBA variants. Patients with GBA variants had faster annual increase in anxiety score (β=0.44; 95%CI, 0.18 to 0.71; p<0.001) and were at higher risk of anxiety progression (HR 1.87; 95% CI, 1.03 to 3.41; p=0.03,).Higher baseline scores for Scales for Outcomes in Parkinson's Disease-Autonomic (SCOPA-AUT) which indicated the autonomic dysfunction also independently predicted faster increase in anxiety score (β=0.48; 95%CI, 0.19 to 0.69; p<0.001) and higher incidence of anxiety development (HR=1.05; 95% CI, 1.01 to 1.08; p=0.008).Interpretation: These findings suggest that longitudinal anxiety symptoms worsening was faster in PD patients who were GBA variants carriers and who have dysautonomia, and this association get enhanced if they have both.